Tindak Pidana Penganiayaan oleh Pengemudi Ojek Konvesional terhadap Pengemudi Transportasi Online - Wahyuni Idrus (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to determine the factors behind the rampant acts of violence by conventional motorcycle taxi drivers against online transportation drivers and to determine the forms of violence experienced by online transportation drivers and the resolution of efforts to overcome them. This study uses an empirical research type, the location of this research is in the Makassar City area and the Makassar Police Headquarters, South Sulawesi Province, located on Jalan Ahmad Yani, by conducting two data collection techniques through literature and field collection techniques such as interviews and observations. The results of this study are the factors behind the rampant acts of violence by conventional motorcycle taxi drivers against online transportation drivers, namely based on factors of jealousy, fighting over passengers, envy, differences in services provided by each online transportation driver with conventional motorcycle taxis and differences in fares and ease of using transportation. While the form of violence experienced by online transportation drivers and the resolution of efforts to overcome it is because online transportation drivers and conventional motorcycle taxis often argue, which usually ends in chaos. Online drivers' motorbikes were also damaged and helmets confiscated for violating conventional motorcycle taxi base areas with agreed pick-ups. At some point, traditional motorcycle taxis lost their market share compared to online transportation, forcing a decrease in passenger volume, but mediation between the two parties involved was able to resolve violent violations in the Makassar City area without having to take legal action. The agreement reached by both parties during the mediation process was the final result.